Analisis Penyebab dan Upaya Meminimalkan Waste Sisa Pemotongan Plastik CPP pada Proses Produksi: Studi Kasus : PT. XYZ - Ricky Dwi Yulianto, Mochammad; Herlina, Herlina (Fakultas Teknik UMRI, 2025)
PT. XYZ is facing a major issue of excessive plastic cutting waste during the CPP plastic production process, particularly at the slitter machine. This waste leads to material overuse, increased production costs, and decreased operational efficiency. This study aims to analyze the root causes of the waste and develop appropriate improvement strategies. The research applies the PDCA (Plan-Do-Check-Action) approach, supported by analytical tools such as the Pareto Diagram, Fishbone Diagram, Fault Tree Analysis (FTA), and Failure Mode and Effect Analysis (FMEA). The findings show that the most dominant type of waste is excessive cutting residue, contributing 80.07% of the total waste. The main cause is identified as a lack of standard cutting tolerance guidelines, categorized under method factors, with the highest RPN score of 320. Improvement strategies focus on SOP revision, operator training, and machine condition control. These efforts are expected to enhance production efficiency and significantly reduce waste.